The role of risk management in improving organizational performance: A field study on private companies in Dammam (The International Journal for Scientific Research, 2026)
This study aimed to identify the impact of risk management with its dimensions (risk identification, risk assessment, risk treatment, risk monitoring) on improving the performance of private companies in Dammam city, Kingdom of Saudi Arabia. To achieve the study objectives, the researcher adopted the descriptive analytical approach and used the questionnaire as the main tool for collecting field data from the study sample members. The study population consisted of employees in private companies in Dammam city, and a stratified random sample of (398) participants was selected from employees at various administrative levels, representing the industrial, commercial, contracting, services, and technology sectors.The study reached several results, most notably the existence of a statistically significant impact at the significance level (α≤0.05) of risk management with its combined dimensions on improving institutional performance, as the dimensions of risk management explained (71.8%) of the variance in improving institutional performance. It was also found that the “risk assessment” dimension is the most influential, followed by “risk treatment”, then “risk monitoring”, and finally “risk identification”. The results showed statistically significant differences in respondents’ perceptions attributed to variables of age, educational qualification, years of experience, and job level, while no differences were attributed to the gender variable.The study recommended that private companies in Dammam should adopt integrated risk management systems, establish specialized organizational units for this purpose, employ modern technologies such as artificial intelligence to enhance risk management capabilities, and establish a risk management culture throughout the entire organization.
Keywords: Risk Management; Risk Identification; Risk Assessment; Risk Treatment; Risk Monitoring; Institutional Performance Improvement; Private Companies; Dammam City; Kingdom of Saudi Arabia